Intercellular delivery of a herpes simplex virus VP22 fusion protein from cells infected with lentiviral vectors - Lai, Zhennan (The National Academy of Sciences, 2000)
Effective gene therapy depends on the efficient transfer of therapeutic genes and their protein products to target cells. Lentiviral vectors appear promising for virus-mediated gene delivery and long-term expression in nondividing cells. The herpes simplex virus type 1 tegument protein VP22 has recently been shown to mediate intercellular transport of proteins, raising the possibility that it may be helpful in a setting where the global delivery of therapeutic proteins is desired. To investigate the effectiveness of lentiviral vectors to deliver genes encoding proteins fused to VP22, and to test whether the system is sufficiently potent to allow protein delivery from transduced cells in vitro and in vivo, fusion constructs of VP22 and the enhanced green fluorescent protein (EGFP) were prepared and delivered into target cells by using HIV-1-based lentiviral vectors. To follow the spread of VP22-EGFP to other cells, transduced COS-7 cells were coplated with a number of different cell types, including brain choroid plexus cells, human endothelial cells, H9 cells, and HeLa cells. We found that VP22-EGFP fusion proteins were transported from transduced cells to recipient cells and that such fusion proteins accumulated in the nucleus and in the cytoplasm of such cells. To determine the ability to deliver fusion proteins in vivo, we injected transduced H9 cells as well as the viral vector directly into the brain of mice. We present evidence that VP22-EGFP fusion proteins were transported effectively from lentivirus transduced cells in vivo. We also show that the VP22-EGFP fusion protein encoded by the lentivirus is transported between cells. Our data indicate that such fusion proteins are present in the nucleus and in the cytoplasm of neighboring cells. Therefore, lentiviral vectors may provide a potent biological system for delivering genes encoding therapeutic proteins fused to VP22.